Pengaruh Likuiditas, Solvabilitas dan Financial Flexibility Terhadap Financial Distress Pada Perusahaan Ritel yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Wahyuni Zamzami; Sri Suartini (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of liquidity, solvency, and financial flexibility on financial distress in retail companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This research uses a quantitative approach with purposive sampling technique, resulting in 22 companies as the sample. Data were collected through financial statement documentation and analyzed using multiple linear regression. The results show that partially, liquidity has a significant effect on financial distress, while solvency and financial flexibility have no significant effect. However, simultaneously, all three variables have a significant effect on financial distress. These findings indicate that the company’s ability to meet short-term obligations is a key factor in determining financial distress. This study is expected to provide insights for investors and management in anticipating financial distress risk.